Increasing food security and nutrition resilience in response to climate change in east Africa: findings from a multisectoral symposium - Paula Braitstein, PhD; Tenzin Lama, MPH; Susan Keino, PhD; Branka Gladanac, MPH; Faith Yego, PhD; Donald Cole, MD; John Simiyu Tabu, PhD; Andrea Cortinois, PhD; Carren Tarus, MPH; Ann Fox, PhD (Elsevier, 2017)
Background: The symposium Kuwa Tayari ("be prepared" in English): finding pathways to nutrition and food security resilience in response to climate change in East Africa was held in Eldoret, Kenya, in May, 2016. The goals of this symposium were to increase awareness, stimulate research ideas and recommendations, catalyse the development of training opportunities, and provide an evidence base for policy and decision-making in these regions in preparation for, and response to, our changing world. Here, we describe the structure, aims, and outcome of the symposium. Methods: The 2-day symposium was a partnership initiative between University of Toronto Dalla Lana School of Public Health in Toronto, Canada, and Moi University, College of Health Sciences, School of Public Health in Eldoret, Kenya. Target audiences were scientists, students, and educators in public health, environmental studies, agriculture, agroecology, civil society, non-government organisations, and government stakeholders. Symposium organisers did a literature review to develop a background paper that helped inform the selection of five planetary health subthemes of the symposium: (1) agriculture, nutrition, and agro-biodiversity; (2) water security; (3) renewable and sustainable cooking fuels; (4) nutrition and food security issues affecting vulnerable populations; and (5) human rights and sustainable development. The symposium format consisted of keynote and oral abstract presentations, plenary discussions, small group work, poster viewing sessions, and networking opportunities. A final report was produced to highlight key outcomes and recommendations. Findings: There were 121 attendees at the symposium from 26 institutions in Kenya, Uganda, Canada, USA, and elsewhere; most were from academic and community organisations. Participants' reasons for attending were met: personal growth and development, networking, research, course and training ideas, and potential collaborations. There was consensus on the need to invest in innovative, context-specific, climate-smart agricultural practices that support sustainable livelihoods and development, and improve food security at the household level throughout east Africa. Interpretation: Multisectoral, transdisciplinary, community-based, and population health research and interventions are needed to address the complex and interconnected issues of climate change, nutrition, and food security. Within east Africa, participatory initiatives that engage vulnerable populations (such as women, pastoral populations, and the urban poor), and those that integrate indigenous food system practices are crucial. Training priorities should be in the areas of integration of climate change topics into existing public health curriculums, and novel interdisciplinary courses on planetary health. Funding: Canadian Institutes of Health Research.